Differentiation Methods for Pendidikan Agama Islam Students Who Come Not from Islamic Boarding Schools and Madrasah Aliyah - Septina Nafiyanti; Dwi Yuwono Puji Sugiharto; Joko Sutarto; Sungkowo Edy Mulyono (International Conference on Science, Education, and Technology, 2023)
Pendidikan Agama Islam became a milestone in the establishment of IAIN Kudus. With the transformation of IAIN Kudus into UIN Kudus, the Program Study of Pendidikan Agama Islam will be in demand by students who do not come from Islamic boarding schools or Madrasah Aliyah (MA). To accelerate learning understanding, a differentiated learning method is needed. The approach used in this study uses a qualitative descriptive research method. The results of this study indicate that the lecturer remembers the name of one student at a time. In addition, lecturers understand student characteristics, learning abilities, learning styles, reading levels, and levels of understanding in absorbing material. The existence of differentiated learning methods makes the learning received between students different from one another. Likewise with different teaching methods. Learning that is created according to the needs and understanding of students.